2016
DOI: 10.1002/lom3.10150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling methods for deep‐sea infauna

Abstract: Sampling methods for benthic meiofauna and macrofauna assessments on the northern Gulf of Mexico continental slope and deep sea were compared. For meiofauna, a core with an inner diameter of 5.1 cm is recommended for yielding an appropriate sample size. Meiofauna are concentrated in the uppermost 2 cm sediment layer, so the top 3 cm are sufficient to sample. Macrofauna penetrate deeper and the top 10 cm are sufficient. Smaller sieves capture more organisms so 45 μm for meiofauna, and 300 μm for macrofauna, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Montagna et al () compared benthic communities collected in the deep Gulf of Mexico at the same place and time by both a multicorer and boxcorer. They found that the boxcorer underestimated macrofaunal abundance by 3x although the multicorer collected 60% fewer taxa than the boxcorer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Montagna et al () compared benthic communities collected in the deep Gulf of Mexico at the same place and time by both a multicorer and boxcorer. They found that the boxcorer underestimated macrofaunal abundance by 3x although the multicorer collected 60% fewer taxa than the boxcorer.…”
Section: Discussionmentioning
confidence: 99%
“…Bow waves from the boxcorer may wash away small, surface dwelling animals during collections (Hulings & Gray, ). The washing and sieving of samples on the boat deck during boxcorer operations may also be responsible for the loss of organisms (Montagna et al, ). However, Montagna et al () found that communities collected via boxcorer and multicorer at the same locations were very different, making comparisons between methods extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations